Da 'città del silenzio' a città delle macchine Prato nel cinema degli anni '50 - Bernardi, Alessandro (Pluriverso - Quaderni della Biblioteca del Polo Universitario di Prato, 2010)
One of the most beautiful films of Italian cinematic Neorealism, Giovanna, a real pearl by Gillo Pontecorvo dated 1955, is almost completely unknown to the public. Entirely filmed in Prato, inside an old factory, now dismantled, and fully interpreted by workers and employees of the various textile companies of the city, the film tells the struggle of the workers to defend their jobs against the thirst for profits of the bosses and also against their own husbands who want them to stay at home to look after the children. It is not only a magnificent document of industrial archaeology, but also and above all the portrait of a new woman, modern and ancient at the same time.